2017
DOI: 10.1002/bab.1513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oligochitosan and oligo‐β‐glucan supplementation on growth, innate immunity, and disease resistance of striped catfish (Pangasianodon hypophthalmus)

Abstract: Oligochitosan (COS) and oligo-β-glucan (βOG) were prepared by gamma Co-60 irradiation of chitosan/H O and β-glucan/H O solutions. The striped catfish (Pangasianodon hypophthalmus) was fed diets containing 0-200 mg COS, βOG, and a mixture of COS/βOG per kg feed for 45 days, and then challenged with Edwardsiella ictaluri bacterium. The effects of supplemented COS, βOG, and a mixture of COS/βOG on immune stimulation and growth performance in striped catfish were investigated. The results indicated that when strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Meanwhile the inclusion of chitin in the diet has no significant effects on fish growth performance [109][110][111], chitooligosaccharide (COS) enhances growth performance parameters such as BWG, hepatosomatic and intestosomatic index, SGR and FCR in a number of fish species, including juvenile largemouth bass (Micropterus salmoides) [112], striped catfish (Pangasianodon hypophthalmus) [113], Nile tilapia (Oreochromis niloticus) [114], tiger puffer (Takifugu rubripes) [115], koi (Cyprinus carpio koi) [116], and silverfish (Trachinotus ovatus) [117]. Similarly as in most fish species, dietary supplementation with low molecular weight and highly deacetylated COS enhances growth performance, innate immunity and digestive enzyme activity in Pacific white shrimp (Litopenaeus vannamei) [118].…”
Section: Dietary Supplementation With Chitin and Chitooligosaccharidementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile the inclusion of chitin in the diet has no significant effects on fish growth performance [109][110][111], chitooligosaccharide (COS) enhances growth performance parameters such as BWG, hepatosomatic and intestosomatic index, SGR and FCR in a number of fish species, including juvenile largemouth bass (Micropterus salmoides) [112], striped catfish (Pangasianodon hypophthalmus) [113], Nile tilapia (Oreochromis niloticus) [114], tiger puffer (Takifugu rubripes) [115], koi (Cyprinus carpio koi) [116], and silverfish (Trachinotus ovatus) [117]. Similarly as in most fish species, dietary supplementation with low molecular weight and highly deacetylated COS enhances growth performance, innate immunity and digestive enzyme activity in Pacific white shrimp (Litopenaeus vannamei) [118].…”
Section: Dietary Supplementation With Chitin and Chitooligosaccharidementioning
confidence: 99%
“…A number of studies showed that both chitin and COS can be potentially utilized as immunostimulants in fish. Respiratory burst activity, phagocytic activity and lysozyme activity, which are considered indicators of non-specific immunity, have been shown to be significantly stimulated by chitin and COS in a number of fish species, including juvenile largemouth bass (Micropterus salmoides) [112], Nile tilapia (Oreochromis niloticus) [114], striped catfish (Pangasianodon hypophthalmus) [113] and mrigal carp (Cirrhina mrigala) [99]. Chitin and COS also induce other immunity parameters, such as nitric oxide production, inducible nitric oxide synthase (iNOS) activity and gene expression [112,120], leukocyte count [99,112,116] and complement activity [99,100].…”
Section: Dietary Supplementation With Chitin and Chitooligosaccharidementioning
confidence: 99%
“…The use of immunostimulants derived from naturally occurring polysaccharides (e.g., β-glucan or chitosan) has become somewhat commonplace in the aquaculture industry as an alternative strategy for disease prevention. Inclusion of oligo-β-glucans (100–200 mg/kg) to striped catfish has shown to improve growth performance and reduce mortality post Edwardsiella ictaluri challenge via heightened phagocytic and lysozyme activity (84). The inclusion of dietary β-glucans (200 mg/kg) in poultry has also been used effectively to reduce the severity of necrotic enteritis when challenged with Eimeria and C. perfringens (85) and inhibited growth depression when challenged with Salmonella enteritidis (86) by increasing specific antibody levels.…”
Section: Dietary Fibermentioning
confidence: 99%
“…Mei et al evaluated the effect of COS on cyclophosphamide (Cy)-induced immunosuppression, and the results implied that delayed-type hypersensitivity (DTH) reaction, macrophage phagocytosis activities, and the levels of cytokines IL-2, IL-12 as well as interferon (IFN)-γ were significantly enhanced while the production of IL-10 was reduced in mice orally treated with COS plus Cy than those exposed to Cy alone [96]. Nguyen et al reported that a remarkable decrease in mortality and enhanced phagocytic activity were observed in striped catfish fed with 100–200 mg COS per kg for 45 days [97]. In continuous feeding of Paralichthys olivaceus with supplementation of 0.5% or 1% COS diets for 28 days, Li et al proved that the leukocyte phagocytic rate, phagocytic index, serum lysozyme activity and the number of peripheral leukocytes were significantly increased.…”
Section: Biological Functions Of Cosmentioning
confidence: 99%